2017
DOI: 10.1186/s12906-017-1779-z
|View full text |Cite|
|
Sign up to set email alerts
|

Toxicity and antitumor potential of Mesosphaerum sidifolium (Lamiaceae) oil and fenchone, its major component

Abstract: BackgroundThe essential oil from Mesosphaerum sidifolium (L’Hérit.) Harley & J.F.B.Pastore (syn. Hyptis umbrosa), Lamiaceae (EOM), and its major component, have been tested for toxicity and antitumor activity.MethodsEOM was obtained from aerial parts of M. sidifolium subjected to hydro distillation, and gas chromatography-mass spectrometry was used to characterize the EOM chemical composition. The toxicity was evaluated using haemolysis assay, and acute toxicity and micronucleus tests. Ehrlich ascites carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
9
0
3
Order By: Relevance
“…The fresh leaves of Mesosphaerum sidifolium afforded an essential oil (ca. 0.6%) rich in limonene ( 244 ), fenchone ( 253 ) and cubebol ( 292 ) ( Rolim et al, 2017 ).…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…The fresh leaves of Mesosphaerum sidifolium afforded an essential oil (ca. 0.6%) rich in limonene ( 244 ), fenchone ( 253 ) and cubebol ( 292 ) ( Rolim et al, 2017 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…The authors reported that the essential oil (100 and 150 mg/kg) and fenchone ( 253 ) (60 mg/kg) were able to reduce all analyzed parameters related to tumor (volume, mass and total viable cells). Furthermore, it was found that both treatments caused a blockage in the cell cycle progression ( Rolim et al, 2017 ).…”
Section: Biological Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the publication of this article [1] it came to our attention that the author list was incorrect. The author Josean Fechine Tavares was included due to an error during the production process.…”
Section: Erratummentioning
confidence: 99%
“…O tumor ascítico de Ehrlich consiste em um modelo de adenocarcinoma mamário, maligno, com alta proliferação e sem remissão, que acomete espontaneamente camundongos (FASTAIA; e, que por suas características quantitativas, é utilizado para testar a influência de fármacos no crescimento ou inibição tumoral (HASHEM et al, 2020;KABEER et al, 2019;ROLIM et al, 2017).…”
Section: Introductionunclassified